2019
DOI: 10.1007/s11547-019-01039-3
|View full text |Cite
|
Sign up to set email alerts
|

Subspecialization in radiology: effects on the diagnostic spectrum of radiologists and report turnaround time in a Swiss university hospital

Abstract: Purpose To analyze the changes in the work profiles of radiologists and the reporting time after the implementation of professional subspecialization in the radiology department of a Swiss university hospital. Methods In a retrospective analysis, the overall number of different radiologic examinations performed in the department of radiology of the largest Swiss university hospital was documented for 2014 and 2016 before and after the implementation of subspecialized reporting (subspecialities: abdominal, musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
2
5
2
1
Order By: Relevance
“…In contrast to the results of Meyl et al [ 3 ], the current study showed particularly that the RTAT for medium-challenging/time-consuming reports, represented by the 80th percentile RTAT, decreased significantly; this is especially true of the RTAT for the subspecialization of musculoskeletal radiology. In the other subspecializations, however, the trend tended towards increased RTATs (Tables 3 and 5 ), which was also observed by other recent studies [ 3 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the results of Meyl et al [ 3 ], the current study showed particularly that the RTAT for medium-challenging/time-consuming reports, represented by the 80th percentile RTAT, decreased significantly; this is especially true of the RTAT for the subspecialization of musculoskeletal radiology. In the other subspecializations, however, the trend tended towards increased RTATs (Tables 3 and 5 ), which was also observed by other recent studies [ 3 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, to other recently published surveys, the present study demonstrated an annual increase of 3.9% in the number of radiology reports and imaging examinations during the evaluation period in 2018 compared to 2017 (Table 1 ) [ 3 , 12 , 13 ]. Interestingly, there was an increase from 37,247 to 38,754 reports but a decrease in reports with a second signature from 16,632 to 15,967 reports (Table 1 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results are in line with those of previous reports (1,8) . In a study conducted by Stern et al (1) , a change from general to subspecialized radiology reporting resulted in a significant decrease in the median TAT, which dropped from 17.04 h to 3.38 h. In another study, subspecialized reporting led to an increase in productivity of approximately 7.0% at one year after implementation (8) . In comparison, we found a 19.70% increase in productively after one year of subspecialized reporting.…”
Section: Discussionsupporting
confidence: 94%